Structures by design thinking, making, breaking - Whitehead, Rob (Routledge, 2020)
Structures by Design: Thinking, Making, Breaking' is a new type of structures textbook for architects who prefer to learn using the hands-on, creative problem-solving techniques typically found in a design studio. Instead of presenting structures as abstract concepts defined by formulas and diagrams, this book uses a project-based approach to demonstrate how a range of efficient, effective, and expressive architectural solutions can be generated, tested, and revised. Each section of the book is focused on a particular manner by which structural resistance is provided: Form (Arches and Cables), Sections (Beams, Slabs, and Columns), Vectors (Trusses and Space Frames), Surfaces (Shells and Plates), and Frames (Connections and High-Rises). The design exercises featured in each chapter use the Think, Make, Break method of reiterative design to develop and evaluate different structural options. A variety of structural design tools will be used, including the human body, physical models, historical precedents, static diagrams, traditional formulae, and advanced digital analysis. The book can be incorporated into various course curricula and studio exercises because of the flexibility of the format and range of expertise required for these explorations. More than 500 original illustrations and photos provide example solutions and inspiration for further design exploration."--Page 4 of printed paper wrapper.